Analisa perkiraan jumlah SDM rekam medik di unit filing dengan metode WISN (Woarl Load Indicator Staff Need) di RSUD Kabupaten Wonogiri Tahun 2014 (Analysis of estimated amount of human resources in the medical record filing with WISN method (Woarl Load I - Alfianto, Lucky; Zakiyah, Erna (IJMS - Indonesian Journal on Medical Science, 2015)
Abstract: Hospital filing officer workload Wonogiri increased with increasing number of patient visits that affect labor productivity, with the condition of filing space inadequate or narrow and inadequate facilities medical record document storage shelves, so that officers found to have to work beyond working hours or delay to resolve day next. The study aims to determine the approximate number of human resources needs in the Medical Record Filing Unit with WISN method in hospitals Wonogiri 2014. descriptive research with observation and interviews, using cross sectional approach, with sampling by the Maytag Company and one officer at the time of observation retrieval and return of medical record. The results showed that the officers carrying out the activity of the organization based on the medical record books Wonogiri District Hospital. Based on the estimated number of patient visits for the period of 2014 a number of 89 639 patients, with an effective amount of working time 1918 hours / year and the average time per principal activity is 0,050 hours can be obtained by standard workload is 38 360 hours / year. When grace is 24 hours per year, then the standard time kelonggarannya 0,012 hours / year. Based on WISN calculation, power requirements of filing in 2014 some 3 HR. Period 2014 Hospital Wonogiri require additional 1 filing officer.Keywords: WISN, working time available, Standard workload, Standard clearances, Quantity principal activities.Â Abstrak: Beban kerja petugas filing RSUD Kabupaten Wonogiri mengalami peningkatan seiring bertambahnya jumlah kunjungan pasien sehingga mempengaruhi produktivitas kerja, dengan kondisi ruang filing yang kurang memadai atau sempit serta kurangnya fasilitas rak penyimpanan dokumen rekam medis, sehingga didapati petugas harus bekerja melebihi jam kerja atau menunda untuk diselesaikan keesokan harinya. Penelitian bertujuan untuk mengetahui perkiraan kebutuhan jumlah SDM Rekam Medik di Unit Filing dengan metode WISN di RSUD Kabupaten Wonogiri tahun 2014. Jenis penelitian diskriptif dengan metode observasi dan wawancara, menggunakan pendekatan cross sectional, dengan pengambilan sampel berdasarkan The Maytag Company dan observasi 1 petugas pada saat pengambilan DRM dan pengembalian DRM. Hasil penelitian menunjukkan bahwa petugas melaksanakan aktivitas berpedoman pada buku penyelenggaraan rekam medis RSUD Kabupaten Wonogiri. Berdasarkan perkiraan jumlah kunjungan pasien untuk periode tahun 2014 sejumlah 89639 pasien, dengan waktu kerja efektif sejumlah 1918 jam/tahun dan rata-rata waktu per kegiatan pokok adalah 0,050 jamÂ dapat diperoleh standar beban kerja yaitu 38360 jam/ tahun. Bila waktu kelonggaran adalah 24 jam per tahun maka standar waktu kelonggarannya 0,012 jam per/tahun. Berdasarkan penghitungan WISN, kebutuhan tenaga filing tahun 2014 sejumlah 3 SDM. Periode tahun 2014 RSUD Kabupaten Wonogiri memerlukan penambahan 1 petugas filing.Kata kunci : WISN, Waktu kerja tersedia , Standar beban kerja, Standar kelonggaran , Kuantitas kegiatan pokok.